2017
DOI: 10.1111/ddi.12569
|View full text |Cite
|
Sign up to set email alerts
|

It is the time for oceanic seabirds: Tracking year‐round distribution of gadfly petrels across the Atlantic Ocean

Abstract: Aim: Anthropogenic activities alter and constrain the structure of marine ecosystems with implications for wide-ranging marine vertebrates. In spite of the environmental importance of vast oceanic ecosystems, most conservation efforts mainly focus on neritic areas. To identify relevant oceanic areas for conservation, we assessed the year-round spatial distribution and spatio-temporal overlap of eight truly oceanic seabird species of gadfly petrels (Pterodroma spp.) inhabiting the Atlantic Ocean. Location: Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 71 publications
2
37
0
4
Order By: Relevance
“…Hence, to capitalize net energy gain, Desertas petrels seemed to rely on a foraging strategy based on covering large distances to increase the probability of encountering foraging opportunities along the route rather than consistently targeting known foraging areas [8,46]. Our results corroborate and build mechanistically upon the findings of previous studies, in which breeding gadfly petrels were found to have a similar foraging strategy, with long foraging trips [4][5][6][7] characterized by low foraging site consistency [6], and long periods of direct flight [4,7], and in which birds travelling for longer distances had higher mass gains [6].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Hence, to capitalize net energy gain, Desertas petrels seemed to rely on a foraging strategy based on covering large distances to increase the probability of encountering foraging opportunities along the route rather than consistently targeting known foraging areas [8,46]. Our results corroborate and build mechanistically upon the findings of previous studies, in which breeding gadfly petrels were found to have a similar foraging strategy, with long foraging trips [4][5][6][7] characterized by low foraging site consistency [6], and long periods of direct flight [4,7], and in which birds travelling for longer distances had higher mass gains [6].…”
Section: Discussionsupporting
confidence: 86%
“…Optimal foraging theory predicts that animals looking for food adopt mechanisms to maximize their energy acquisition per unit time and minimize their energy loss [1][2][3]. The constraints faced by breeding oceanic seabirds-patchily distributed resources and having to return to their colony to alternate incubation shifts with the partner-result in sometimes spectacular foraging trips, many thousands of kilometres from the colony [4][5][6][7]. Seabirds thus have morphology and flight behaviour adapted to glean energy for these long commutes from the wind.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most knowledge of its distribution at sea comes from shipbased sightings (Enticott 1991, Orgeira 2001. More recently, its general phenology and distribution were summarized together with other gadfly petrels species using tracking data (Ramos et al 2017). However, Ramos et al (2017) did not include detailed descriptions on its phenology and spatial ecology, the factors influencing migration schedules within the population or other important aspects of its at-sea ecology, such as habitat preferences, at-sea activity patterns and moulting strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Given the logistical challenges of observing animals within the dynamic nature of polar environments, the application of animal telemetry devices has revolutionized our understanding of the movement ecology of marine species (Hussey et al, 2015). Telemetry data have provided novel insights into complex, previously unknown behaviours, including predator-prey interactions (Breed et al, 2017), fishing fleet interactions with fishes and seabirds (Queiroz et al, 2016;Rolland, Barbraud, & Weimerskirch, 2008;Tuck, Polacheck, Croxall, & Weimerskirch, 2001), environmental drivers of habitat use (Amélineau et al, 2018;Block et al, 2011;Raymond et al, 2015), species diversity hotspots (Grecian et al, 2016) and identifying critical conservation areas (Dias et al, 2017;Lascelles et al, 2016;Ramos et al, 2017). Traditionally, telemetry studies on Arctic marine predators have focused on single or a few species.…”
mentioning
confidence: 99%